Renuncia de Benedicto XVI a la Sede Petrina. Aspectos canónicos - Ciudad Albertos, Antonio (Estudios eclesiásticos, 2013)
«Well aware of the seriousness of this act, with full freedom I declare that I renounce the ministry of Bishop of Rome, Successor of Saint Peter […] in such a way, that as from 28 February 2013, at 20:00 hours, the See of Rome […] will be vacant and a Conclave to elect the new Supreme Pontiff will have to be convoked». This surprising words of Benedict XVI, announced on 11 February 2013, have situated all of us in front of the possibility of the Petrine office resignation, as well as the essential elements to be valid.